LACTIC ACID BACTERIA MICROBIOTA OF “PIROT`S KASHKAVAL” - BOJANA, D.; NEBOJŠA, M.; DRAGOLJUB, C.; DRAGIŠA, S. (Italian Journal of Food Science, 2020)
“Pirot`s kashkaval” represents an autochthonous dairy product belonging to pasta-filata cheeses. In order to determine the changes in the lactic acid bacteria microbiota during 60 days of ripening, 315 lactic acid bacteria strains isolated from ewe`s and cow`s milk cheese were identified as Enterococcus faecium, Pediococcus acidilactici, Pd. pentosaceus, Lactobacillus casei/rhamnosus, Lb. plantaum, Lb. casei, Lb. fermentum, Lb. paracesei, Lb. rhamnosus and Streptococcus macedonicus. Enterococci were the most dominant strains. In the final stages of ripening, the increase of the population of Lb. casei and Pd. acidilactici was observed for ewe`s and cow`s milk cheese, respectively.